Renegosiasi dan Restrukturisasi Perusahaan dalam Upaya Peuyelesaiau Hutaug - Aman Sentosa (Fakultas Hukum Universitas Islam Indonesia, 2000)
The settlement mechanism of credit through re-negotiating credits and restructuring company will achieve efficiency and increase productivity which Is indicated hydecreasing the company's problems, and increasing company's income; thus the company will be able to settle its credits. In this Indonesian crisis era, an effective method of credit settlement is required. The efforts and the methods to settle are discussed in this article.